Religion-Adapted Cognitive Behavioral Therapy: A Review and Description of Techniques - Abreu Costa, Marianna de (Journal of religion and health, 2022)
Systematic reviews have shown the efficacy of religion-adapted cognitive behavioral therapy (R-CBT); however, many clinicians lack practical knowledge of these protocols. We describe here the techniques of religious adaptation to CBT that have proved effective. We selected randomized clinical trials comparing R-CBT with control conditions in clients with a diagnosis of a psychiatric disorder and extracted the information from their adapted manuals. The most frequent religious adaptations were the integration of religious content to perform cognitive restructuring, psychoeducation and motivation; engagement in religious activities such as behavioral activation, meditation, or prayer to help cognitive restructuring, using religious values and coping strategies. A description of these techniques is presented here, as well as some practical examples.